IDENTIFIKASI DAN PEMANFAATAN TANAMAN OBAT DI KECAMATAN TALANG KELAPA KOTA PALEMBANG - Hiras Habisukan, Ummi; Suhertini, Rizky (Universitas PGRI Adi Buana Surabaya, 2024)
Medicinal plants are plants that can be used for curing the diseases because of its compounds. Identification of medicinal plants is needed to consider the kinds ofmedicinal plants. This study aims to know the species used as medicine and to process it for curing disease. This study is qualitative descriptive. The sampling technique is quota sampling with triangulation and data were analized by Miles and Huberman model. The results showed that 38 species from 22 family of medicinal plants aere found. Parts that are widely used were leaves, then roots, stems, flowers, flower petals, fruit, rhizomes, sap, tubers and all parts. Based on this study it can be seen that these plants can treat various diseases, including diabetes, hypertension, cholesterol, fever, diarrhea, skin itching caused by fungi such as phlegm and ringworm, vaginal discharge and nosebleeds, thrush, increase and accelerate breast milk production, accelerates the healing process of wounds and relieves menstrual pain. The most popular management method was boiled. Another method was mashed and then rubbed, dripped, dried and then affixed, brewed and consumed directlyas vegetables, vegetables or other food mixes.